2019
DOI: 10.3389/fmicb.2019.01131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Rumen Microbiota of Beef Calves Supplemented During the Suckling Phase

Abstract: A study was conducted to examine the effects of supplementing beef calves during their suckling phase (popularly known as creep feeding) with supplements that contained or did not contain the enzyme xylanase. Forty-two cow-calf pairs were divided into three groups and assigned to one of three treatments for a period of 105 days, as follows: (1) No supplemental feed for calves (control; CON); (2) Corn and soybean meal-based supplement feed for calves (positive control; PCON); and (3) Same feed regimen as PCON w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…As stated before, Prevotella was the most abundant genus detected in the ruminal samples, and its average abundance was greater in the creep fed calves. Previous research from our group [17] also observed that the presence of Prevotella was increased in the rumen of creep fed calves. That study also identified a positive correlation between abundance of Prevotella and calf average daily gains.…”
Section: Composition Of Microbiotas At the Genus Levelsupporting
confidence: 67%
See 1 more Smart Citation
“…As stated before, Prevotella was the most abundant genus detected in the ruminal samples, and its average abundance was greater in the creep fed calves. Previous research from our group [17] also observed that the presence of Prevotella was increased in the rumen of creep fed calves. That study also identified a positive correlation between abundance of Prevotella and calf average daily gains.…”
Section: Composition Of Microbiotas At the Genus Levelsupporting
confidence: 67%
“…The complete Illumina library was purified with SPRI-beads (1:1 ratio) and sequenced on an Illumina MiSeq using a v3 600 cycle kit (Illumina, San Diego, CA) at the Georgia Genomics and Bioinformatics Core. Negative controls were used throughout extraction and PCR procedures, and used KAPA reagents (KAPA Biosystems, Wilmington, MA) as described in detail in a previous study [17].…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…After overnight storage, the samples were transported to the Georgia Genomics and Bioinformatics Core ( https://dna.uga.edu ) for library preparation and 16S rRNA gene sequencing. The library preparation included PCR replications using the forward primer: S-D-Bact-0341-b-S-17 (5′-CCTACGGGNGGCWGCAG-3′) and reverse primer: S-D-Bact-0785-a-A-21 (5′-GACTACHVGGGTATCTAATCC-3′) ( 13 , 14 ). PCR conditions were: initial denaturation at 95°C for 3 min, followed by 25 cycles of 95°C for 30 s, annealing at 55°C for 30 s, extension at 72°C for 30 s, and then a final elongation step at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Upon arrival at the slaughter facility, rumen fluid was individually collected from all steers following the procedures described in Lourenco et al [18]. Briefly, this procedure utilized esophageal tubing and a perforated metal probe, which is attached to an electric vacuum pump for collection of the ruminal contents.…”
Section: Rumen Content Collection and Storagementioning
confidence: 99%